Analisis Potensi Kebangkrutan Dengan Menggunakan Model Prediksi Finansial Distrees Ohlson, Grover, Altman Z-Score Pada Perusahaan Property & Real Estate - Yohanes Reva Cahyo K; Maria Magdalena PD (Jurnal Solusi, 2018)
The Property Industry will experience an increase or decrease in profit making. So, the company must anticipate that the company does not experience financial distress or lead to colaps. Because the company has a goal that utilizes existing sources of funds and resources as optimal as possible so that the company does not suffer losses that can ultimately lead to colaps. Industry Property in Indonesia is increasingly dragged into large debt and is part of the global property company debt that has accumulated. Debt of global property companies is said to reach US 25 trillion, and domestic developers are affected because almost all property companies are owned by foreign investors.